Association Between Dieting Failure and Unconscious Hedonic Responses to Food - Sato, Wataru (Frontiers in Psychology, 2020)
Dieting is a popular but difficult strategy for reducing weight. Previous studies have revealed several psychological characteristics associated with dieting failure. Here the hypothesis that dieting failure is associated with unconscious hedonic responses to food was tested with a subliminal affective priming task. Food image primes or their scrambled mosaic primes were subliminally presented. Participants scored their liking of the subsequent target ideographs. The participants’ subjective dieting success was additionally assessed using questionnaires. Differences in liking scores of target ideographs between the food and mosaic conditions, as well as liking scores of target ideographs under the food condition by partialling out other effects, were negatively associated with dieting success scores. These results suggest that dieting failure is associated with the strength of unconscious hedonic responses to food and that environmental controls to reduce food cues may be needed for dieting success.